COVID 19 quarantine and its impact on lifestyle of diabetic patients and on their follow up in Madinah, KSA (Journal of Pharmaceutical Negative Results, 2022)
Objectives: This article aims to discover the impact of the coronavirus pandemic lockdown on diabetes patients living in Almadina, Saudi Arabia, in terms of their lifestyle and on their follow-up. Methods: This is a cross-sectional, qualitative prospective study, a questionnaire was done to diabetic patients who underwent the quarantine period in Madinah, Saudi Arabia through an online questionnaire after getting informed consent to participation. The survey included personal, medical data, patient’s compliance to treatment and overall lifestyle manner before and during lockdown period and psychological assessment using 10 questions of the (K10) Kessler psychological distress scale. Data analysis was performed using SPSS program version 26. Results: A total of patients 350 participated in the study. 56.6% of them were females(n;198), and 43.4% were males(n:152), their ages ranged from 18 years to more than 60 years. The vast majority 96.3% of participated were of Saudi nationality, while 3.7% are non-Saudi. Participants-with types 2 Diabetes represent 31.4% while 26% suffer from type 1 diabetes and the rest they don’t which type they have. Results showed no significant differences in: (symptoms of low or high blood sugar, the extent to which a healthy diet is followed, the frequency of home blood sugar measurement) before and during the quarantine period. The rest of the variables shows a significant difference (P<0.05) Conclusions: The study showed a difference in the extent of adherence to medication during the quarantine period compared to before. A reduction constructive in lifestyle habits is detected.